Reactions of Dichlorotris (Triphenylphosphine) Ruthenium(II) with Various Sulfur Ligands - Bhowon, M.G.; Reedoy, H. (Asian Journal of Chemistry, 2010)
Reactions of dichlorotris (triphenylphosphine) ruthenium(II) with various sulfur ligands such as m-(mercaptoacetamido) phenol m-(MAP), thioacetamide, cyanothioacetamide have been described. These compounds were characterized by analytical, magnetic and spectroscopic (UV, Vis, IR) data.